KEPENTINGAN KANADA DALAM PEMBEBASAN AKTIVIS PEREMPUAN SAUDI, SAMAR BADAWI - Nurhafiza, Khairunnisa; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the interests underlying Canada’s involvement in urging the release of Saudi Arabian women’s rights activist Samar Badawi. Using a qualitative approach and case study method, the research examines the dimensions of Canada’s foreign policy grounded in democracy, human rights, and international feminism. Data were collected through literature review of official documents, media reports, and relevant diplomatic statements. The findings reveal that Canada’s support for Samar Badawi was not solely driven by a normative commitment to human rights issues, but also constituted part of a soft power strategy to strengthen its global image as a defender of liberal values. Through public statements, diplomatic notes, and engagement in international forums, Canada sought to assert its position as a consistent advocate of human rights. However, such actions triggered diplomatic tensions with Saudi Arabia, reflecting the dilemma between public diplomacy and moral imperatives. The study concludes that the Samar Badawi case illustrates the practice of value-based public diplomacy intertwined with national strategic interests, while also underscoring the complexity of implementing public diplomacy within the dynamics of global politics. Keywords: Women’ Rights, Segregation, Activist, Patriarchy, Interests, State, Human Right.